Changes in The Aging Cytoskeleton and How Metformin Plays a Role in Delaying Aging - Dini, Dini; Achadiyani, Achadiyani; Khairani, Astrid Feinisa (Universitas Aisyah Pringsewu, 2024)
The cytoskeleton plays an important role in forming the cell framework and dynamics. The part that plays a role in supporting the spatial and mechanical functions of the cell is located in the cytoskeleton. Therefore, strategies to maintain the integrity and dynamics of the cytoskeleton have potential as therapies for age-related disorders. One thing that can be used to delay aging is metformin. Through AMPK activation, it can influence the cytoskeleton; namely, it can remodel the dynamics of the cytoskeleton by influencing structural changes in the actin cytoskeleton, which in turn will reduce the permeability of the filtration barrier in diabetic conditions and can increase insulin sensitivity, especially in old age, thereby delaying aging. In this review, we review the current understanding of the role played by the cytoskeleton in aging and review the opportunities and challenges for transitioning basic research into intervention development. Methods: Several major electronic databases, including PubMed, Scopus, and Cohcrane were used to select articles between April 2013 and April 2023. From the 8 existing literature, we present the activity of metformin as an aging delay. Cytoskeleton can change with age so it can affect the dynamics and structure of the cell. Metformin shows significant benefits, especially in delaying aging, through activation of the AMPK pathway so that it can increase the activity of mitochondria in producing ATP, which can affect the structure of the cytoskeleton. With this article on changes in the cytoskeleton with aging, it is hoped that insight into future research directions can be achieved.